Management model to become a teacher during university education - Kozhushkova, Natalia V. (2021)
The article reveals the problem of becoming a teacher, training of a teacher with a high intellectual level of self-awareness, capable of conceptual thinking, creative activity and ready for independent management of his own professional activity, which will allow him to interact with the learning environment more effectively, to be an active subject of professional and pedagogical activity.